Anatomy and Physiology 2e - Betts, J. Gordon; Young, Kelly A.; Wise, James A (Open textbook library., 2021)
Anatomy and Physiology 2e is developed to meet the scope and sequence for a two-semester human anatomy and physiology course for life science and allied health majors. The book is organized by body systems. The revision focuses on inclusive and equitable instruction and includes new student support. Illustrations have been extensively revised to be clearer and more inclusive. The web-based version of Anatomy and Physiology 2e also features links to surgical videos, histology, and interactive diagrams. Please learn more about the changes by previewing the preface.